GEOINFORMATION EXPERT-MODELING COMPLEX OF RESEARCH OF REGIONAL MODELS IN GEOLOGY - Dolynskiy, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Modern studies in the field of geology on the basis of modeling tools necessarily end with the construction of a three-dimensional geological model, which, in turn, is the basis for making technological and financial decisions in assessing the quality and prospects of deposits and mines. In geology, there are usually two generalized types of geological models. Models of local objects, for which there is a dense information grid with available data for their construction, and regional models in which the input information is liquid and unevenly distributed. Regional objects can be built from local objects and additionally form lacking geological and geophysical information through various methods. The problem of constructing models of local objects can be considered solved, because there is a sufficient number of software products for constructing and conducting research with them (Petrel Schlemberger, Geographix Landmark, etc.). The question of constructing regional geological models remains open and the problem of creating methodologies for their creation and evaluation should be considered relevant. The regional geological model refers to the digital model of a large geological structure, which includes local objects, which are its constituent parts and represent structures of higher orders. The author proposes special software components for constructing digital models of regional objects, which are simply embedded in existing industrial geological modeling tools, and will take into account such a distribution of source information and constructed models that enable them to perform qualitative evaluation. The article presents the functional capabilities of the geoinformation expert-modeling complex (GEMK), which provides: creation of models of regional objects, their storage, processing and visualization of geological and geophysical information available to them for spatial analysis and evaluation of model quality. The offered approaches provided an opportunity to programally implement a user-friendly software complex for the construction and analysis of regional geological objects. The cartographic interface of the system uses common geological terminology and is oriented to a specialist geologist-geophysicist. The system is tested on real geological material. GEMK is implemented in the form of a geographic information system with built-in means of simulation of regional geological models of geology. The complex consists of three software components developed in various development environments and integrated into the ArcView project using DLL technology. In functional terms, the considered program components of this complex realize the possibilities: 1) the construction of 2D models of geological boundaries, lithological and capacitive filtration parameters, taking into account the full complex of source and a priori information on the basis of standard Geomapping tools; 2) simulation of 3D visualization of the constructed models; 3) spatial analysis of models for the purpose of developing and adopting engineering solutions for the effectiveness of the assessed areas for which regional models are built. The corresponding software was created on the basis of available and industrial GIS ArcView 3.n using built-in software elements that implement specialized modeling and evaluation techniques for geological objects. The system was tested on the geological sites of the main oil and gas province of Ukraine - the Dnipro-Donets depression.